Convergence Theorems of Multi-Valued Generalized Nonexpansive Mappings in Banach Spaces (Global Journal of Science Frontier Research, 2023)
In this paper we study multi-valued generalized nonexpansive mappings in uniformly convex Banach spaces We introduce multi-valued version of the iterative scheme presented in 4 and prove some weak and strong convergence results in uniformly convex Banach space Further we present an illustrative numerical example of approximating fixed point of multi-valued generalized nonexpansive mappings satisfying condition E considering multivalued version of the iterative scheme presented in 4
Keywords: generalized nonexpansive mappings; multi-valued mapping; fixed point; iteration process; uniformly convex banach spaces